SOSIALISASI TERAPI JUS BELIMBING (AVERRHOA CARAMBOLA) DALAM MENURUNKAN TEKANAN DARAH PADA LANSIA DENGAN HIPERTENSI DI WILAYAH KERJA UPTD PUSKESMAS MUNJUL JAYA PURWAKARTA - Herwed Nelson D; Grace, Grace; Reiyan Budi Kusuma (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
Hypertension is one of the most common health problems experienced by the elderly and is a major cause of morbidity and mortality in Indonesia. The use of natural ingredients as a supportive therapy is an effective and safe option. Star fruit (Averrhoa carambola) contains potassium, fiber, vitamin C, and antioxidants that function to help lower blood pressure through vasodilation and increased sodium excretion. This activity aims to increase the knowledge and skills of the elderly community and health cadres regarding the benefits and how to make star fruit juice as a non-pharmacological therapy to lower blood pressure in elderly with hypertension. The activity was carried out through socialization and direct demonstrations to 25 elderly participants with hypertension in the work area of ​​the Munjul Jaya Community Health Center (UPTD), Purwakarta. Evaluation was carried out through pre- and post-tests of knowledge, as well as blood pressure observations before and after drinking star fruit juice for 5 consecutive days. There was an increase in the average knowledge score of participants from 65% to 92% after the socialization. The average blood pressure of the elderly also decreased from 157/92 mmHg to 139/84 mmHg after regularly consuming starfruit juice. Participants stated that starfruit juice is easy to make, delicious, and has no side effects. The promotion of starfruit juice therapy effectively increased public awareness and helped lower blood pressure in the elderly. This activity can be used as a model for promotive and preventive interventions in hypertension control at the primary care level